The Differentiation of Gender Bias Paradigm Toward The Qanun Aceh Number 6 of 2014 on Jinayat Law - Jarudin Jarudin; Salma; Ade Saputra; Ihsan Muhidin (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
Qanun Aceh Number 6 of 2014 on Jinayat Law, which was amended through Aceh Qanun Number 12 of 2025 concerning Amendments to Aceh Qanun Number 6 of 2014 on Jinayat Law, has been implemented for more than a decade and continues to attract national and international attention. Several provisions related to sexual violence have been criticized by gender observer groups through the List of Inventory Problems (DIM), particularly the requirement for female rape victims to provide evidence beyond their own testimony. Critics argue that this provision burdens victims and potentially hinders access to justice. This article also highlights that rape provisions were absent from the initial draft of the Qanun, indicating that the regulation emerged through a complex and contested legislative process. This study employs qualitative field research using primary and secondary data collected through interviews and documentation. Data were analyzed through reduction, display, and verification techniques, supported by sharia, normative-juridical, and empirical-juridical approaches. The findings reveal contrasting perspectives between the Qanun drafters and critics. The drafters view the Qanun as reflecting Islamic legal principles emphasizing repentance over imprisonment, while critics point to inconsistencies with the Indonesian Criminal Code (KUHP), enforcement challenges, and elements of gender bias. This study’s novelty lies in its analysis of the legislative trajectory of rape provisions within the Jinayat Qanun and its examination of how tensions between Islamic legal values, human rights discourse, and gender justice continue to shape the reform and implementation of Jinayat law in contemporary Aceh.